A STUDY ON THE ABILITY OF THE SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU IN CHANGING ACTIVE SENTENCES INTO PASSIVE VOICE - Maryulis, Renny; Azhar, Fadly; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive study aim to find out students’ ability in changing active sentences into passive voice, The study was conducted at the second semester students of English Study Program FKIP Universitas Riau. There were 37 students as the sample of this finding. The data were collected by administering a test to the students in the form of written test and were analyzed by using quantitative technique. The findings of the study are following: a.students’ score in changing active sentences to passive voice in simple past tense in the form of positive sentences is 63.00, b.students’ score in changing active sentences into passive voice in simple past tense in the form of negative sentences is 53.51, c.students’ score in changing active sentences into passive voice in simple present tense in the form of positive sentences is 67.02, d.students’ score in changing active sentences into passive voice in simple present tense in the form of negative sentences is 67.56, e.students’ score in changing active sentences into passive voice in simple future tense in the form of positive sentence is 52.4, f.students’ score in changing active sentences into passive voice in simple future tense in the form of negative sentences is 53.51. This finding can be concluded that the highest score was in changing active sentences into passive voice in simple present tense 67.56, which categorized into good level, and the lowest score is in changing active sentences into passive voice in simple future tense in the form of positive sentence 52.43 which categorized into mediocre level. The implication of the finding is that the second semester students of English Study Program FKIP Universitas Riau should improve their ability in understanding the formulas for each tenses of passive voice, so they can change active sentences into passive voice properly and correctly in order to reach excellent level.Key Words: Ability, Changing, Active sentence, Passive voice